2019
DOI: 10.1177/1043986219842014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Spatial Patterns of Police Activity and Mental Health in a Canadian City

Abstract: Mental health–related calls for service are increasing across Canadian communities. However, the spatial dynamics of these calls for service and their potential relationship with concentrations of crime has not been fully investigated in the Canadian context. The current study examines mental health and other calls for service in a medium-sized (approximate population of 250,000), midwestern Canadian city in the year 2014. Using kernel density analysis and a spatial point pattern test, the study explores the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
8
29
0
Order By: Relevance
“…The purpose of this study was to explore the rate and geographic distribution of 911 calls for service related to mental health issues during the COVID-19 pandemic in the City of Detroit, MI, USA. This study is similar to other recent attempts to explore the relationship between the COVID-19 pandemic and levels of crime and police calls for service (see, for example, Ashby, 2020a , 2020b ; Felson et al , 2020 ; Hodgkinson and Andresen, 2019 , 2020 ; Mohler et al , 2020 ; Stickle and Felson, 2020 ). The results of the instant study were somewhat counterintuitive in that the total number of calls for mental health issues was at the lowest level when compared to the same time period for the previous 3 years.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The purpose of this study was to explore the rate and geographic distribution of 911 calls for service related to mental health issues during the COVID-19 pandemic in the City of Detroit, MI, USA. This study is similar to other recent attempts to explore the relationship between the COVID-19 pandemic and levels of crime and police calls for service (see, for example, Ashby, 2020a , 2020b ; Felson et al , 2020 ; Hodgkinson and Andresen, 2019 , 2020 ; Mohler et al , 2020 ; Stickle and Felson, 2020 ). The results of the instant study were somewhat counterintuitive in that the total number of calls for mental health issues was at the lowest level when compared to the same time period for the previous 3 years.…”
Section: Discussionsupporting
confidence: 76%
“…Other researchers have reported similar concentrations of mental health calls for service (see, e.g. Hodgkinson and Andresen, 2019 ; White and Goldberg, 2018 ) While areal concentrations have been previously reported, what impact (if any) does the COVID-19 crisis have on the geography of mental health calls for service?…”
Section: The Geography Of Mental Healthmentioning
confidence: 65%
“…In using street segments as the unit of spatial analysis -that is, both sides of the street from intersection-to-intersection (Eck & Weisburd, 1995) -previous research on the concentration of PwPMI calls for service has found that 50% of calls occur on a very small percentage of segments: between 0.30 and 3% (Hodgkinson & Andresen, 2019;Vaughan et al, 2016Vaughan et al, , 2019White & Goldberg, 2018). This same work as also found that, although PwPMI calls are highly concentrated, the calls are dispersed within that concentration.…”
Section: Spatial Concentrations Of Police-pwpmi Calls For Servicementioning
confidence: 99%
“…This same work as also found that, although PwPMI calls are highly concentrated, the calls are dispersed within that concentration. In other words, PwPMI calls for service tend to cluster in multiple hot spots that are spread out across the jurisdiction (Hodgkinson & Andresen, 2019;Vaughan et al, 2016;White & Goldberg, 2018). Further, PwPMI calls for service have also been found to be highly concentrated at larger spatial units (Vaughan et al, 2019).…”
Section: Spatial Concentrations Of Police-pwpmi Calls For Servicementioning
confidence: 99%
See 1 more Smart Citation